1996
DOI: 10.1590/s0100-84551996000400020
|View full text |Cite
|
Sign up to set email alerts
|

Maternal age and Down syndrome in Southeastern Brazil

Abstract: The proportion of maternal-age-independent patients estimated among 200 Brazilian Down syndrome children (59.6%) was significantly larger than that of maternal-age-dependent cases (40.4%). The latter proportion is the smallest observed in pertinent literature and due basically to the low mean maternal age of the population analyzed. Based on the remarkable correlation (r = 0.95) between the proportion of maternal-age-dependent patients and the mean maternal age of the general population, a simple predictive eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
7

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 5 publications
1
4
0
7
Order By: Relevance
“…A Brazilian study conducted in the southeastern region of the country showed that the maternal age of women with DS children was significantly higher than that of women without DS children (Beiguelman et al, 1996), and our results confirm this finding.…”
Section: Discussionsupporting
confidence: 87%
“…A Brazilian study conducted in the southeastern region of the country showed that the maternal age of women with DS children was significantly higher than that of women without DS children (Beiguelman et al, 1996), and our results confirm this finding.…”
Section: Discussionsupporting
confidence: 87%
“…3,4 In fact, it has been shown that the frequency of chromosomal aberrations becomes greater with advancing maternal age, 3,24,25 especially with regard to trisomy of chromosomes 13, 18 and 21 in women who give birth when over 35 years old. 26 According to data from the Latin American Collaborative Study of Congenital Malformations (ECLAMC), 40% of live births with DS were born from mothers who were between 40 and 44 years old, although women of this age account for only 2% of all births.…”
Section: Discussionmentioning
confidence: 99%
“…2 The risk factors for meiotic nondisjunction are not very clear, except for advanced maternal age. 3,4 Folic acid has an important role in the process of genetic material distribution during cell division, because of its importance to cellular methylation reactions. 5 The folate metabolism is responsible for synthesizing S-adenosylmethionine (SAM), the main donor of methyl groups for cellular methylation reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Com relação a maior prevalência de conhecimento da condição sindrômica da criança após o nascimento, o estudo de Suneilaitis (11) observou que ao saber sobre o diagnóstico crônico e com tantas limitações como a SD, torna-se difícil a elaboração da perda do filho " imaginário" pelas mães. Associa-se a isto a transmissão de orientações do profissional, que deverá ser atualizado, a fim de fornecer informações para aquela etapa da vida da criança, sempre acentuando as possibilidades de desenvolvimento em todas as áreas: afetiva, social e cognitiva quando estas forem estimuladas adequada e precocemente.…”
Section: Discussionunclassified